Relative linguistics theory and ancient Arabic grammar - Al-Ansary, Ryhanah Abdullah (Arab Journal for Sciences and Research Publishing, 2020)
This research came to discuss in a few pages the importance of linguistic development and renewal, and the rise of Arabic thought to Innovation, and in this field, Dr. Mohamed Al-Uraghi highlighted a shiny thought that urges the renewal of knowledge, Moving to a higher level of linguistic thinking, and came with the theory of relatively linguistic, To start a new development in the field of the language study, The research pointed to criticism of the old Arabic grammar way to exceed criticism to development and renewal of the Oragi approach in the language lesson.The research referred to criticism of Arabic grammar, presented by Al-Oraghi, and the legitimacy and validity of this criticism, in a descriptive methodology comparative analysis, and the research reached several conclusions, the most important of which is the incorrectness of replacing Arabic grammar with the theory of relativism.
Keywords: Critique of Grammar; Standard Grammar; Relativism